Assessment of the Impact of COVID-19 Pandemic on Tourism and Hospitality Sector Evidence from the South Asian Countries (Global Journal of Management and Business Research, 2023)
The aim of this study is to explore the overall effect of COVID-19 pandemic on tourism and hospitality industry of Bangladesh and India This research utilized journals historical records newspaper articles World Health Organization statistics governmental data and website materials on COVID-19 incidences in tourism Secondary research was adopted in which secondary data were collected through a comprehensive literature review The COVID-19 outbreak has significantly affected global travel and tourism Bangladesh and India has also experienced an adverse impact on inbound and outbound tourism International and domestic tourists have cancelled bookings in both country and outbound tourism activities have also been banned Airlines have cancelled flights while hotels are almost completely vacant and as a result supporting tourism agencies are facing huge economic losses and employment cuts in Bangladesh and India The intensification of COVD- 19 is predicted to cause a long-term adverse impact on tourism both in Bangladesh and India The government of Bangladesh and India government has declared an incentive package for early economic recovery that is needed for businesses to survive the pandemic
Keywords: COVID-19 pandemic; tourism and hospitality; bangladesh; india